ANALISIS FAKTOR-FAKTOR YANG MENINGKATKAN KEPERCAYAAN PELANGGAN MELAKUKAN ONLINE SHOPPING DAN DAMPAKNYA TERHADAP MINAT BELI ULANG (Studi pada Pelanggan Online Shopping di Kota Tangerang) - Tarto Tarto; Yanthi Meitry Gunawan (Faculty of Economics and Business, Universitas Malikussaleh, 2019)
The purpose of this study was to analyze how much influence the knowledge of internet technology, company quality and website quality on customer trust, the effect of product quality and customer trust on risk perceptions and their impact on repurchase interests in online shopping customers in Tangerang City. The research sample is 98 online shopping customers in Tangerang City. The sampling technique used convenience sampling. Data collection distributed questionnaires via email. The method used in this study is the verification method to determine the influence of knowledge of company quality internet technology and website quality on customer trust, the influence of product quality and customer trust on perceived risk and its impact on repurchasing interests in online shopping customers in Tangerang City. The test statistics used are designing structural models, designing measurement models, building flowcharts, testing the appropriate models. Suitability test of structural models and hypotheses using SmartPLS 3.0 software.